The Implementation of Learning Station Method in Teaching Report Text to Improve Students' Motivation and Learning Outcomes - Lazarurizqi, Galih Jodi; Kamil, Acep Bahrum (IKIP Siliwangi, 2025)
Many junior high school students struggle to learn English and are unmotivated, especially when it comes to learn report texts, which are frequently thought of as boring. By using the Learning Station paradigm to improve academic achievement and motivation, this classroom action research sought to solve this problem. The study, which used pre-tests, post-tests, observation and interviews, was carried out in Class 9C at SMP Negeri 1 Karawang Timur over the course of two instructional cycles. The results showed that student outcomes had significantly improved, with average scores increasing from 64.08 to 77.76 and higher levels of desire and motivation. The Learning Station approach to learn report text made the classroom lively and fun by alternating activities between reading, writing, discussion, and interactive stations. Students expressed increased confidence and motivation.